Breath and Air Analysis: Applications in Resource-poor Settings. (2015) - Riley, Alison; Krisher, Sarah; Mehta, Khanjan
Abstract: Recent research developments have led to the emergence of various portable and affordable gaseous-compound detecting devices. These non-invasive technologies detect volatile organic compounds in human breath or air, providing important information about us and our environment. While many of these technologies have been seamlessly integrated into Western countries, they have yet to be leveraged in developing nations. These devices can be used to easily and affordably screen patients for diabetes, monitor air quality of cities, and facilitate agricultural intensification. This article describes five scenarios where breath and air analysis technologies can address problems faced by populations in resource-poor settings.